Serum cystatin C as a potential biomarker for generalized acetylcholine receptor antibody-positive myasthenia gravis - He, Dingxian; Zhong, Huahua; Jin, Lei; Chen, Ran; Wu, Zongtai; Zhao, Rui; Huan, Xiao; Yan, Chong; Song, Jie; Xi, Jianying; Zhao, Chongbo; Zhu, Shanfeng; et al. (Frontiers in Immunology, 2025)
ObjectiveTo identify new metabolic biomarkers associated with myasthenia gravis (MG).MethodsWe analyzed 285 potential metabolic molecules from UK Biobank (UKB) for MG patients and identified elevated serum cystatin C (Cys-C). Validation was performed using laboratory data, ELISA, and clinical information from Chinese (CHN) acetylcholine receptor antibody (AChR-Ab) positive generalized MG (gMG) cohorts. We assessed cytokines/chemokines/complements and peripheral blood T lymphocytes using Luminex assays and flow cytometry. MG-relevant scores including myasthenia gravis activities of daily living score (MG-ADL) and quantitative myasthenia gravis score (QMG) were prospectively collected and retrospectively analyzed. The correlations between serum Cys-C and the ratio of T helper 1 (Th1)/Th2 were assessed.ResultsSerum Cys-C levels were significantly elevated in MG patients compared to healthy controls in both UKB cohorts and Chinese MG cohorts (CHN) (UKB: 0.99 ± 0.20 vs. 0.86 ± 0.12 mg/L, p = 2.26E-41; CHN: 1.08 ± 0.30 vs. 0.87 ± 0.13 mg/L, p = 4.83E-08). Higher serum Cys-C levels were found in MG patients with high disease burden, as stratified by MG-ADL score. Serum Cys-C correlated with MG scores, including QMG (R = 0.40, p = 3.90E-03) and MG-ADL scores (R = 0.42, p = 2.40E-03). The ratio of Th1/Th2 correlated well with the serum Cys-C (R = 0.29, p = 3.10E-02).ConclusionsSerum Cys-C levels were significantly elevated in AChR-Ab positive gMG patients and correlated with disease severity and Th1/Th2 ratio, suggesting its potential as an efficient biomarker for predicting the clinical severity of MG. Future prospective cohort studies with a large sample size are expected to validate these findings.